1973
DOI: 10.1111/j.1432-1033.1973.tb02586.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Structure of Yeast tRNAPhe

Abstract: The availability of (yeast)tRNAPhe for helix formation with complementary oligoribonucleotides has been explored by equilibrium dialysis studies. Oligoribonucleotides complementary to sequences which are double-stranded, according to the cloverleaf model of tRNAPhe, did not bind. Two regions of tRNAPhe were fully acessible to oligonucleotide binding: (a) the 3'-terminus; (b) the sequence (3'-5')U-G-A-A-Y (33-37) of the anticodon loop. Two other regions were accessible to oligonucleotide binding: (a) part of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

1977
1977
1996
1996

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(22 citation statements)
references
References 28 publications
3
19
0
Order By: Relevance
“…Oligo-. nucleotide binding studies to E. coli tRNAMet,E, coli tRNA Tyr [3], and yeast tRNA Phe [8]. have shown, that these tRNA's have an asymmetric anticodon loop structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Oligo-. nucleotide binding studies to E. coli tRNAMet,E, coli tRNA Tyr [3], and yeast tRNA Phe [8]. have shown, that these tRNA's have an asymmetric anticodon loop structure.…”
Section: Resultsmentioning
confidence: 99%
“…T~OC Pu represents the sequence which is common to all tRNA's so far sequenced. Since in the four tRNA's examined by oligonucleotide binding studies [2,3,8], T~OC is available to complementary GAA binding, it might indicate a common environment as well as function of this particular tRNA sequence.…”
Section: Resultsmentioning
confidence: 99%
“…The increased complex formation with U-U-C-A cannot be explained by a higher population of the stacked conformer in the tetranucleotide as compared to the trinucleotide, because U-U-C-C shows a lower association constant as compared to U-U-C-A [2].…”
Section: Introductionmentioning
confidence: 97%
“…It has been shown that complementary tetranucleotides only bind effectively to the C-C-A end and the anticodon region of the tRNA [1,2]. Extensive studies have been performed using either oligonucleotides and cognate tRNAs or tRNA pairs with complementary anticodons to elucidate the structural details for codon-anticodon recognition [3][4][5]7].…”
Section: Introductionmentioning
confidence: 99%
“…Equilibrium dialyses were performed in plexiglass cells, as in [7]. The solvent for all experiments was 0.2 M NaCl + 0.04 M MgClz + 1 mM sodium phosphate (pH 7.4).…”
Section: Elsevierlnorth-holland Biomedical Pressmentioning
confidence: 99%